Experimental analysis of cold-formed steel columns with intermediate and edge stiffeners in fire. (January 2020) - Laím, Luís; Craveiro, Hélder D.; Simões, Rui; Escudeiro, André; Mota, Alexandre
Abstract: Although the use of longitudinal stiffeners in cold-formed steel members in compression is known to increase their ultimate strength at ambient temperatures, it is expected that the rigidity of such stiffeners and the strength of steel decreases when the cold-formed steel members are exposed to high temperatures. Therefore, this paper presents and discusses the results of an experimental investigation on the structural response of cold-formed steel columns with intermediate and edge stiffeners under fire conditions for assessing mainly their critical temperatures, critical times (fire resistance) and failure modes. The main variables studied included the: (a) cross-section shape, (b) boundary conditions, (c) edge stiffener configuration and (d) stiffness of the surrounding structure to the thermal elongation of such columns. Additionally, European fire design predictions (EN 1993-1-2:2005) were compared with the experimental results, in order to observe their accuracy. Finally, based on the findings of this research work it is obvious the advantage of using CFS sections with double edge fold stiffeners over the sections with single edge fold stiffeners. Moreover, built-up sections had lower critical temperatures than those for single sections, but with slightly higher fire resistance time. Furthermore, existing analytical methods have been shown to be incapable to predict sufficiently realistic the complex buckling behaviour of restrained CFS columns under fire conditions. Highlights: Experimental investigation on the structural response of stiffened cold-formed steel columns under fire conditions. The effect of different cross-section shapes, boundary conditions and edge stiffener configurations were evaluated. The effect of stiffness of the surrounding structure to the thermal elongation of such columns was studied. CFS sections should be improved in the way of getting rigid closed hollow flanges. The design calculation methods developed for hot-rolled members may be unsafe for such CFS members.